CROSSWORD PUZZLE SEBAGAI MEDIA EDUKASI KESEHATAN MENSTRUASI PADA REMAJA PUTRI - Saputra, Mukhammad Himawan; Dwi Helynarti Syurandhari; Arief Fardiansyah (JURNAL PENGABDIAN MASYARAKAT KESEHATAN (ABDIMAKES), 2025)
Adolescent girls are a vulnerable group in terms of reproductive health, particularly regarding the lack of understanding about menstrual hygiene management (MHM), which can affect both physical and psychological well-being. This community service program aimed to improve adolescent girls’ knowledge of MHM through the use of educational games, specifically crossword puzzles. The activity included a pre-test and post-test, material delivery by health students, and interactive learning using crossword puzzles. It was conducted at SMPN 2 Mojoanyar on January 22, 2025, involving 35 female students aged 12 to 15 years. The evaluation results showed a significant increase in knowledge, with the percentage of participants in the good category rising from 17.1% to 57.1% after the intervention. The game-based media proved effective in creating an engaging, participatory learning environment and enhancing information retention. This activity concludes that crossword puzzles are a viable educational strategy for adolescent health promotion in schools. Similar approaches are recommended to be implemented sustainably in other educational institutions.